How exceptional is Australian financial sector misconduct? The Hayne Royal Commission revisited. Issue 2 (2nd April 2020) - Singleton, John; Reveley, James
Abstract : By failing to consider that the types of financial misconduct witnessed in Australia in recent years are relatively commonplace in other countries, the Hayne Royal Commission exaggerates the level of miscreance within the local financial sector. This paper seeks to rectify this neglect by offering an explicit comparison of misconduct in Australian and major British and American banks. It also suggests that the Commission's work and findings inadvertently provide support for the populist view that Australian financial institutions are exceptionally unethical in their treatment of customers and clients. Given the emergence of Fintech and the potential for Big Tech firms to penetrate financial services markets, large incumbent Australian firms are already facing a serious challenge. If the net effect of the Royal Commission is to deepen mistrust of large Australian banks and insurers, their capacity to resist this challenge will be diminished with potentially far-reaching consequences.